Personality and Social Context Factors Associated to Self-Reported Excessive Use of Information and Communication Technology (ICT) on a Sample of Spanish Adolescents - Martín-Perpiñá, Maria de las Mercedes; Poch, Ferran Viñas; Cerrato, Sara Malo (Frontiers in Psychology, 2019)
• The vulnerability that characterizes adolescents justifies the growing health concern about the impact of excessive use of ICT. Exploring the roll both psychological and social variables in excessive use of ICT in adolescents can help preventing risk behaviors. • Examining the ICT use of 1,102 secondary school, baccalaureate and professional training course students (11-18 years old, M = 14.42, Sd = 1.78; 50.58% boys), we investigate the psycho-social profile of those adolescents who have self –reported an excessive use of ICTs. Personality factors were assessed using the NEO-FFI, and social context factors through the PWI (Personal Well-being Index); AF5 (Multidimensional Scale of Self Concept); SSA (Social Support Appraisals); ad hoc questions on self-perception of parental and sibling ICT consumption, and the existence of rules for ICT use in the home. 14.5% (n = 160) of adolescents match the criteria of excessive use. The self-reported excessive use is associated as much by personality factors as by family context. Risk factors in self-reported excessive adolescent ICT use are being female, impulsiveness, perceiving a high level of family support and a high use by parents and siblings. The family, academic, emotional and physical self-concepts are factors of protection. This study has provided us with a profile of adolescents who make a self-reported excessive use of ICT, which may be of help in preventing such use. The presence of these specific personality and socio-demographic factors indicate a greater vulnerability and may serve as indicators for parents, teachers and healthcare professionals to intervene and prevent excessive ICT use and other serious psychological problems related.